2013
DOI: 10.1159/000351010
|View full text |Cite
|
Sign up to set email alerts
|

Disability in Instrumental Activities of Daily Living in Elderly Patients with Mild Cognitive Impairment and Alzheimer‘s Disease

Abstract: Background/Aims: The aim is toexamine disability in instrumental activities of daily living (IADL) in elderly persons with mild cognitive impairment (MCI) and Alzheimer‘s disease (AD), further to identify items of IADL which separate the two conditions and to explore potential gender differences. Methods: A cross-sectional study of 729 patients aged ≥65 years recruited from outpatient memory clinics. Multiple logistic regression analysis was used in the main analysis to explore the association between IADL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 55 publications
2
27
0
1
Order By: Relevance
“…This may also assist in validating complex IADL change as a further clinical characteristic observed in eMCI. Studies have indeed found increased sensitivity of IADL scoring in the MCI demographic, once scores are split into complex and simple categories [48,49].…”
Section: Discussionmentioning
confidence: 98%
“…This may also assist in validating complex IADL change as a further clinical characteristic observed in eMCI. Studies have indeed found increased sensitivity of IADL scoring in the MCI demographic, once scores are split into complex and simple categories [48,49].…”
Section: Discussionmentioning
confidence: 98%
“…In this cohort that has previously been reported as having high levels of newly-acquired cognitive impairment 11 , the duration of delirium was not associated with either disability outcome (i.e., IADL or ADL status), a finding in contrast to disability outcomes in populations with similar levels of cognitive impairment such as mild cognitive impairment and Alzheimer's disease. 43 While in need of further study in survivors of critical illness, the difference in these outcomes could be explained by differing underlying pathologies between these syndromes, the potential for functional disability to be expressed differently in cognitively impaired ICU survivors than individuals with progressive dementia, the neuropsychiatric domains that are impaired, or simply that the data supporting an association between cognition and functional status are conflicting and in some cases modest. 44 At least 2 studies in medically ill cohorts – one in ICU patients 45 and one in patients following surgery 46 – have demonstrated an association between delirium and ADL disability, in contrast to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of ADL should be a part of a dementia workup, but Hesseberg at al. [5] show that impairment in ADLs is not always considered when diagnosing people with symptoms of dementia. Feedback from colleagues and subjects in our study indicates that the items of the CFI are functions and activities that represent well the functional decline seen in the early stages of dementia.…”
Section: The Importance Of Assessing Early Activity Problemsmentioning
confidence: 99%